The use of your own voice in labor: a phenomenological study - Priscila Paiva de Almeida Mendonça; Letícia Becker Vieira; Valéria Lindner Silva; Marcele Zveiter (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To understand the meaning attributed by women to the use of their own voice in labor. Method: Descriptive qualitative study based on the theoretical-philosophical-methodological framework of Heidegger. Phenomenological interviews were carried out with 20 women who experienced vaginal delivery without interventions in the second quarter of 2020 in the city of Rio de Janeiro - Brazil. Results: The comprehensive analysis revealed that the voice can provoke a reaction from the environment that makes them suffer. The expression of the voice encompasses fear and despair. It is from what they hear that women fear being left in suffering for havingbothered the professionals. Conclusion: The meaning of using one's own voice in childbirth was understood as a request for help or an expression of freedom. Based on this understanding, the professionals can be opened to sensitive and individualized care, which goes beyond technology.